Pengaruh Kreativitas Industri dan Pengembangan Kewirausahaan Terhadap Tingkat Kesejahteraan Pada Usaha Bordir - Magfirah Magfirah; Sri Wahyuni; Idaryani Idaryani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this study was to analyze the effect of creativity and entrepreneurial development on the level of welfare of embroidery business craftsmen in Peusangan District, Bireuen Regency. In this study using primary data, namely embroidery business craftsmen in Peusangan District, Bireuen Regency with a total of 52 businesses. Data collection techniques using a questionnaire. The data analysis model used is multiple linear regression analysis. The results of the study stated that creativity affects the level of border welfare in Peusangan District, Bireuen Regency. Entrepreneurial development also influences the welfare level of embroidery business in Peusangan Dostrict, Bireuen Regency. This shows that border business craftsmen must have creativity that can be used to improve their welfare. On the other hand, the business must be developed considering that this factor also affects the welfare of the business. Creativity and entrepreneurship development are two things that must be done if the craftsmen want their welfare to be increased.